DISIPLIN PEGAWAI DALAM PENGGUNAAN ATRIBUT KEPANGKATAN PADA SEKRETARIAT DAERAH PROVINSI BENGKULU - Junaidy, Chefran (Jurnal Governance dan Administrasi Publik, 2017)
This study is to determine the Employee Discipline In Using Attribute Ranks In Bengkulu Provincial Secretariat in accordance with the Governor Regulation No. 14 of 2013 on uniforms and attributes of civil servants in the Department of Government of Bengkulu Province. This is a qualitative research method. Sample interviews in this study were taken from the 6 elements 2 and 4 structural officials staff. The sampling technique used in this study sampling purposive research that took respondents by researchers consideration. Data analysis was conducted through interviews with how repetitive and continuous between data collection and analysis, either during data collection in the field and after the data are collected. Data analysis was performed by 3 stages: reduction, Display, and inference and verification. The results showed discipline in the use of Attribute Ranks Employee uniforms Protection Society and Clothing Department Warana Legs In Bengkulu Provincial Secretariat in accordance with the Governor Regulation No. 14 of 2013 on uniforms and attributes of civil servants in the Department of Government of Bengkulu province in the implementation has not been optimal. This is because there are many staff or employees who do not comply with usage attribute uniforms, such as the employee does not use the Board Names, Name / ID Card, Signs Rank, Name Tag, WTP and Belt, Badges Korpri.